THE INFLUENCE OF THE INTENSITY OF ACCESSING THRIFT CONTENT ON TIKTOK AND PEER GROUP COMMUNICATION ON THE PURCHASE INTENTION OF THRIFT FASHION AMONG INDONESIA'S GENERATION Z - Bryan Anugerah Firdaus; S. Rouli Manalu (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
The development of social media has transformed information consumption patterns and consumer behavior, including the phenomenon of thrift fashion purchasing among Generation Z. TikTok has become one of the most widely used platforms for accessing information related to thrift products, while communication within peer groups may also influence individuals’ purchasing decisions. This study aims to examine the influence of the intensity of accessing thrifting content on TikTok and peer group communication on thrift fashion buying intention among Generation Z in Indonesia. The study employs the Theory of Reasoned Action (TRA) as its theoretical framework. This research uses an explanatory research design with a quantitative approach. The population consists of Generation Z TikTok users in Indonesia, with a sample of 114 respondents selected through cluster sampling. Data were collected through an online questionnaire and analyzed using multiple linear regression with SPSS software. The findings indicate that, simultaneously, the intensity of accessing thrifting content on TikTok and peer group communication significantly influence thrift fashion buying intention, with a coefficient of determination of 37.2%. Partially, the intensity of accessing thrifting content on TikTok has a positive and significant effect on thrift fashion buying intention, with a significance value of 0.010 (<0.05), while peer group communication does not have a significant effect, with a significance value of 0.531 (>0.05). The study concludes that the intensity of accessing thrifting content on TikTok plays a more dominant role in shaping thrift fashion buying intention among Generation Z than peer group communication.